KEWENANGAN DINAS KEBUDAYAAN PROVINSI RIAU DALAM MELESTARIKAN KEBUDAYAAN MELAYU DI PROVINSI RIAU TAHUN 2019-2020 - Farhan Filya Oktama; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Authority is formal power that comes from legislation. The Cultural Office of Riau Province is a Regional Apparatus Organization that has the authority to preserve Malay culture in Riau Province. Today, Malay culture is fading in the midst of society. This study aims to find out how the authority of the Riau Provincial Cultural Office in preserving Malay culture in Riau Province in 2019-2020 and to find out the causes of the Riau Province Cultural Office not being maximized in preserving Malay culture in Riau Province. The method used in this research is descriptive method with qualitative research type. The types of research data are primary data and secondary data. The data analysis technique used is descriptive qualitative data analysis.The results of this study are the authority of the Riau Provincial Cultural Office in preserving Malay culture in 2019-2020, the Riau Provincial Cultural Office refers to the Riau Governor Regulation Number 82 of 2016 concerning the Position, Organizational Structure, Duties and Functions and Work Procedures of the Riau Province Cultural Service Article 15-Article 18 which in carrying it out is given the freedom to take policies in terms of preserving Malay culture in Riau Province. The causes of the Riau Provincial Cultural Service not being maximal in preserving Malay culture in Riau Province in 2019-2020 are the very low or small budget for the Riau Provincial Culture Service, the incoming culture from outside due to the swift and unstoppable flow of globalization and the covid-19 pandemic.  Keywords: Authority, Conserve, Culture